2020
DOI: 10.2147/nss.s263528
|View full text |Cite
|
Sign up to set email alerts
|

<p>Astroglial Mechanisms Underlying Chronic Insomnia Disorder: A Clinical Study</p>

Abstract: The objective of this study was to investigate whether the serum biomarkers S100 calcium binding protein B (S100B), glial fibrillary acidic protein (GFAP), brain-derived neurotrophic factor (BDNF), and glial cell line-derived neurotrophic factor (GDNF) change in patients with chronic insomnia disorder (CID), and if this is the case, whether the altered levels of these serum biomarkers are associated with poor sleep quality and cognitive decline in CID. Patients and Methods: Fifty-seven CID outpatients constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…In addition, our previous study showed that CID patients had significantly increased serum levels of astrocyte biomarkers and we speculated that CID patients may have pathological changes in their astrocytes. 42 , 43 It is therefore possible that SAA, produced in the central or peripheral nervous system, could influence the development of insomnia symptoms by activating microglial cells and inducing proinflammatory cytokine production. It is important to note that this study only cross-sectionally investigated the levels of potential biomarkers in CID patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our previous study showed that CID patients had significantly increased serum levels of astrocyte biomarkers and we speculated that CID patients may have pathological changes in their astrocytes. 42 , 43 It is therefore possible that SAA, produced in the central or peripheral nervous system, could influence the development of insomnia symptoms by activating microglial cells and inducing proinflammatory cytokine production. It is important to note that this study only cross-sectionally investigated the levels of potential biomarkers in CID patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous study showed that CID patients had significantly increased serum levels of astrocyte biomarkers and we speculated that CID patients may have pathological changes in their astrocytes. 42,43 It is therefore possible that SAA, produced in the central or peripheral nervous system, could influence the development of insomnia symptoms by activating microglial https://doi.org/10.2147/NSS.S310698…”
Section: Discussionmentioning
confidence: 99%
“… 59 Patients with chronic insomnia disorder exhibited increased GFAP serum levels, which could indicate some degree of astrocyte damage. 60 Mice with chronic sleep deprivation showed low-grade neuroinflammation, anxiogenic response and recognition memory impairment, accompanied by enhanced expression of GFAP in brain regions. 61 Consistent with these evidences, expression level of GFAP was negatively correlated with sleep health score in our PWAS results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the relief/remission of their illness may not be accompanied by normalization of changed protein levels (damage of astrocytes structure may be a trait) (16). Subjects with CID also exhibit significantly lower levels of glial cell line-derived neurotrophic factor (GDNF) and brain-derived neurotrophic factor (BDNF) than healthy people (17). These findings strongly implicate astrocyte dysfunction in CID, but more evidence is needed to support this hypothesis (17).…”
Section: Introductionmentioning
confidence: 99%
“…Subjects with CID also exhibit significantly lower levels of glial cell line-derived neurotrophic factor (GDNF) and brain-derived neurotrophic factor (BDNF) than healthy people (17). These findings strongly implicate astrocyte dysfunction in CID, but more evidence is needed to support this hypothesis (17). Additional studies are needed to investigate other astrocyte-related markers to better understand the mechanism of CID.…”
Section: Introductionmentioning
confidence: 99%